Heterogeneous Catalytic Oxidation of Aqueous Phenol on Red Mud-Supported Cobalt Catalysts - Muhammad, Syaifullah; Saputra, Edy; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (American Chemical Society, 2012)
Red mud (RM), an industrial waste from the alumina refinery industry, was used as a support for preparation of Co-oxide-based catalysts (Co/RM). The samples were characterized by N2 adsorption, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and UV-vis diffusive reflectance spectroscopy. The heterogeneous catalytic activity was evaluated in aqueous phenol degradation using peroxymonosulphate (PMS) as an oxidizing agent. It was found that Co3O4 particles were highly dispersed on the RM surface and that pretreatment of the red mud (RM-T) would significantly influence catalytic activity. Co/RM-T catalysts exhibited high effectiveness in heterogeneous activation of PMS to produce sulfate radicals for phenol degradation compared with Co/RM-NT. Phenol degradation followed first-order kinetics, and activation energies on Co/RM-T and Co/RM-NT are 46.2 and 47.0 kJ/mol, respectively.